Revue française de sociologie (Centre d'études sociologiquesgParis [Tb1], 2001)
The Revue Française de Sociologie is published in paper form and electronically (in French). Additionally, since 2012, all articles published in the RFS have been translated into English. The English version is published electronically within six months after the French version.